Automatización del proceso de fumigación para la prevención de plagas en el galpón N° 2 en la granja avícola Sánchez durante el periodo 2021. - Sánchez Cruz, Christian Daniel (2021)
The present research project was implemented in shed No. 2 of the Sanchez poultry farm in the city of Baños de Agua Santa to design and implement an automated system for the control of the fumigation and disinfection process inside the shed No. 2, optimizing this process. The automation of the process was initiated through information gathered at the poultry farm where the problem of non-technical and non-automatic spraying was observed. The system consists of four stages starting with the "liquid filling" where electrovalves and water level sensors act, "product dosing" (disinfectant), the actuators are electrovalves and water level sensors, "liquid mixing" activates a mixing paddle driven by a motor coupled to a gearbox and the "fogging process" where 96 foggers were installed inside the poultry house, distributed in 6 rows of 125 PSI hose. The main control module of the electrical panel is a PLC S7 1200 CPU 1212 AC/DC/Relay programmable logic controller. A human-machine interface (HMI) was incorporated, which provides control and visualization of the variables fumigation and mixing time, the quantity of water and product liquid, nebulization pressure, etc. With the implementation of the automated system for fumigation control, efficiency results are obtained in the process, and the main objective of fumigation is to treat the maximum possible surface area, helping to prevent, control and mitigate the entry, transmission, and exit of pathogenic agents that generate a negative impact on the production system; these measures are necessary to maintain egg safety and provide a better quality product.